Analisis Pemberdayaan Perempuan Kelompok Petani Kopi Di Desa Bancea - Melani Prisccilia Mokonio; Silvany Annatje Taariwuan; Charis Elfis Fajar Sangkide; Feliks Arfid Guampe (Madani: Jurnal Ilmiah Multidisiplin, 2023)
The purpose of this study was to determine the empowerment of women coffee farmers in Bancea Village, South Pamona District. This study used a qualitative descriptive method by collecting data through interviews and observations of members of the Katundana coffee farmer group in Bancea village and 1 agricultural officer in Bancea village. The results of this study are that women coffee farmers in the village of Bancea are empowered in farming and processing Kojo coffee. They are equipped with knowledge, skills and facilities to support their jobs and work programs. This empowerment provides positive benefits for increasing the level of welfare of women in their households and also economic development in the village.